(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Romanian Culture and Religious Character at the Encounter Between Sacred Text and Oral Tradition in the Context of Identity Crises.Identity of people comes from all those specific cultural and traditional values that give a particular and unique character among other nations. Culture is more than a package of notions that admit existence of set of rules and specific particularities shown in a group of behaviors that appeared and grew up sporadically, but more is a projection of traditions build around of sacred word. The sum of all traditions and behaviors represent the outline of nation, and we can identify and analyze it during the past of history. Christianity represent the environment of free expression of faith and liberty of worship and transcendent connection given to each person is an divine act offered by God through creation. More that that, the liberty and human rights represent the expression of Gospel message that brings the ethnic, social and gender barriers around the common message. The new perspective create the base of particular evolution of own identity, defined by own cultural particularities with unique characteristics. The context of Romanian religious culture shapes types of thinking and interpretation, give behaviors templates and relational between people and entire community. An strong accent of religious culture is represented by the material and spiritual values that can be noticed in all segments of life – familial, ecclesial and social.